Molecular Imaging of Fibrosis in Benign Diseases: An Overview of the State of the Art - Yongbai Zhang; Wenpeng Huang; Hao Jiao; Lele Song; Lei Kang (MDPI AG, 2024)
Fibrosis is a progressive pathological process participating in the progression of many diseases and can ultimately result in organ malfunction and failure. Around 45% of deaths in the United States are believed to be attributable to fibrotic disorders, and there are no favorable treatment regiments available to meet the need of blocking fibrogenesis, reversing established fibrosis, and curing diseases, especially in the terminal stage. Therefore, early detection and continuous monitoring provide valuable benefits for patients. Among all the advanced techniques developed in recent years for fibrosis evaluation, molecular imaging stands out with its distinct advantage of visualizing biochemical processes and patterns of target localization at the molecular and cellular level. In this review, we summarize the current state of the art in molecular imaging of benign fibrosis diseases. We will first introduce molecular pathways underlying fibrosis processes and potential targets. We will then elaborate on molecular probes that have been developed thus far, expounding on their mechanisms and current states of translational advancement. Finally, we will delineate the extant challenges impeding further progress in this area and the prospective benefits after overcoming these problems.